Pengaruh krisis keuangan global dan karakteristik perusahaan terhadap cash holding perusahaan di Indonesia - Bambang Sutrisno; Tatang Ary Gumanti (Jurnal Siasat Bisnis, 2016)
The aim of this study is to examine the effect of the global financial crisis and firm characteristics on corporate cash holdings in Indonesia. A total of 101 manufacturing firms listed in the Indonesia Stock Exchange from 2005 to 2014 are examined. This study employs panel regression with fixed effect model. The results show that Indonesia firms hold more cash during the global financial crisis than in the normal times. Investment opportunities set and divident payment have positive effect on cash holding, meanwhile firm size, capital expenditure, liquid assets substitutes, and leverage have negative effect on cash holding.